Study of Gastropod Community Structure After Development of Tourism Activities on the Senjoyo River - Marsahanda Astri Ramagita; Sucahyo Sucahyo; Desti Christian Cahyaningrum (Jurnal Natur Indonesia, 2023)
It is thought that the development of the Senjoyo River as a tourist attraction in Semarang Regency will cause changes to the natural ecosystem in the area, one of which is changing the structure of the existing gastropod community. This research is a quantitative analysis research using a survey method that aims to examine the structure of the gastropod community after the development of tourism activities on the Senjoyo River. Gastropod samples were taken from 10 different observation stations along the Senjoyo River, which are located at 7˚22'23"S and 110˚31'37"E. Observation station locations were determined by the purposive random sampling method, based on tourism activity density. The result showed types of gastropods that were found in the Senjoyo River namely, Sulcospira testudinaria, Tarebia granifera, Brotia costula, Thiara scraba, and Melanoides tuberculata with clustered distribution patterns (Id>1). Statistical analysis showed that location affected gastropod abundance (Asymp. Sig of 0.043), with the highest abundance found at station seven (45,11 individuals/m2). So station seven, with sandy and muddy substrate conditions, moderate current speed (0.257 m/s), and rarely found human activity, is the most suitable location to support the survival of gastropods in the Senjoyo River. Furthermore, the gastropod community structure indicates environmental changes at observation stations nine and ten, the locations where the most activities and construction of tourism facilities were found. That was indicated by the low diversity (H’= 0.00-0.01) and evenness (E = 0.00) index of gastropods, and there is dominance by Sulcospira testudinaria (C= 0.98-1.00).